Cartografia institucional das reestruturações no sistema estadual de extensão rural na região Sudeste do Brasil - Souza, Fernanda Maria Castro de (Universidade Federal de São Carlos, 2025)
The work analyzes the historical process of formation, consolidation, and restructuring of public Institutions of Technical Assistance and Rural Extension (ATER) in the states of the Southeast Region of Brazil, focusing on the trajectory of EMATER-MG, EMATER-RIO, INCAPER-ES, and CATI-SP. A documentary and bibliographic analysis was carried out, covering state legislation, institutional reports, historical memorials, and academic publications that address the evolution of rural extension in the country. From the creation of the first Rural Credit and Assistance Associations in the 1940s and 1950s, through the national coordination carried out by ABCAR and later by EMBRATER, which was dissolved in 1989, marking a turning point, generating systemic disarticulation and requiring each state to autonomously reconfigure its ATER structure, which resulted in different arrangements in the Southeast region. Minas Gerais managed to maintain institutional continuity, consolidating a stable network of offices and participatory methodologies. In Espírito Santo, the integration between research and extension gave rise to Incaper, which is considered today a model of articulation between technology generation and transfer. São Paulo structured its own system through CATI, prioritizing decentralization and municipal technical support. Meanwhile, Rio de Janeiro experienced a path marked by political-administrative instabilities, mergers, and changes in affiliation. It is concluded that, although rural extension remains strategic for family farming and territorial development, its current effectiveness depends on stable funding, state policies, and the appreciation of the technical staff, since state systems still reflect the historical inequalities and disruptions that marked their formation.
Institutional mapping of restructuring in the state system of rural extension in the Southeastern region of Brazil
Keywords: Extensão rural; Assistência técnica; Políticas públicas; Rural extension; Technical assistance; Public policies; Family farming; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL; 2. Fome Zero e Agricultura Sustentável